A Subset of Oligodendrocyte Lineage Cells Interact With the Developing Dorsal Root Entry Zone During Its Genesis - Green, Lauren A.; Gallant, Robert M.; Brandt, Jacob P.; Nichols, Ev L.; Smith, Cody J. (Frontiers in Cellular Neuroscience, 2022)
Oligodendrocytes are the myelinating cell of the CNS and are critical for the functionality of the nervous system. In the packed CNS, we know distinct profiles of oligodendrocytes are present. Here, we used intravital imaging in zebrafish to identify a distinct oligodendrocyte lineage cell (OLC) that resides on the dorsal root ganglia sensory neurons in the spinal cord. Our profiling of OLC cellular dynamics revealed a distinct cell cluster that interacts with peripheral sensory neurons at the dorsal root entry zone (DREZ). With pharmacological, physical and genetic manipulations, we show that the entry of dorsal root ganglia pioneer axons across the DREZ is important to produce sensory located oligodendrocyte lineage cells. These oligodendrocyte lineage cells on peripherally derived sensory neurons display distinct processes that are stable and do not express mbpa. Upon their removal, sensory behavior related to the DRG neurons is abolished. Together, these data support the hypothesis that peripheral neurons at the DREZ can also impact oligodendrocyte development.